Sucrose Tolerance Test in Children With Diarrhoea - Widiarto Widiarto; Teluk Sebodo; Irawan Irawan; Widayat Widayat; Ismangoen Ismangoen (Paediatrica Indonesiana, 1982)
A study of Sucrose Tolerance Test has been done in 30 children with the ages ranging between 11!2 and 18 months suffering from diarrhoea who were admitted to the Department of Child Health, Gadjah Mada University Hospital, Yogyakarta during November 1979 until April 1980.Ten out of 30 children (33.33%) had blood sugar level increase more than 40 mg%, and one of them developed diarrhoea, while 20 out of 30 children (66.67%) had blood sugar level increase less than 40 mg%, one of them developed diarrhoea.